Rapid and Extensive Collapse from Electrically Responsive Macroporous Hydrogels. Issue 4 (12th September 2013) - Kennedy, Stephen; Bencherif, Sidi; Norton, Daniel; Weinstock, Laura; Mehta, Manav; Mooney, David
<x xml:space="preserve">Abstract</x> Electrically responsive hydrogels are created with interconnected macropores, which greatly enhance their ability to rapidly undergo volumetric collapse when subjected to moderate electric fields. When optimized, these electrogels are easily integrated into arrays capable of rapid configurational and chromatic optical modulations, and when loaded with drugs, are able to coordinate the delivery profile of multiple drugs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>